Unmanned Safety Survelliance For Railroad Crevices - et. al., Durga Lakshmi M, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Railroads give the least expensive and most helpful method to travel and goods transportation for both short and long distance. Still mishaps are the significant worry due to unidentified break in rail lines, resulting in the loss of precious lives and economic loss. As a result, a durableand reliable invention for crack detection in railroad tracks is needed. In the proposed system, a robot is developed that automatically navigates using the L293D motor driver and detects the railroad crevices. The system automatically detects the crack using IR sensor attached to the robot, which will continuously monitor the crack. The IR sensor detects a crack and transmit a signal to the Raspberry Pi, which triggers the GPS receiver. The global positioning system(GPS) receiver will trace the exact location and trigger a message to the concerned person through GSM module. Furthermore, itwill activate the webcam, which will provide a live feed of the rail line. In case the robot detects any object using ultrasonic sensors the warning message will be sent with the location to take the further action and Vibration sensor is used to detect vibrations of the upcoming train.